Physicians Emigration between the Right to Emigration and Patients Right to Health Care: A Comparative Study - Benfifi, Taqiyeddine (Indonesian Journal of Social Science Research, 2024)
This study aims to shed light on the dilemma of physicians’ emigration and health care through two perspectives that are arguably conflicting. More specifically, the objective of this paper is to examine the fundamental rudiments of these two perspectives. While the first perspective focuses on the multifaceted right of physicians to emigrate which is represented predominantly by the liberalist, the second perspective focuses on the right of patients to obtain necessary health care provided by physicians, this approach is represented by the nationalists. To achieve our aim, the comparative method was used which is adequate in presenting the underlying premises of each approach after reviewing the existing literature. By extracting the main basic conjectures and refutations of contradictory statements and analyzing it profoundly, the study findings indicated that the advocate of physicians’ mobility is pointedly linked to patients’ health care, and any shortage in physicians due to departing will impact health care accessibility. The findings also suggest that both of the perspectives carry rational and realistic arguments, but the differences in the assumptions and the reductionism of the claims hinders and prevents the possibility of reconciling and combining them in order to reach a solution to what can be called the discrepancy dilemma of rights between physicians’ emigration and patient health care.